Radiographic Contrast-Media-Induced Acute Kidney Injury: Pathophysiology and Prophylactic Strategies. (16th September 2013) - Sadat, Umar
Abstract : Contrast-induced acute kidney injury (CI-AKI) is one of the most widely discussed and debated topics in cardiovascular medicine. With increasing number of contrast-media- (CM-) enhanced imaging studies being performed and growing octogenarian population with significant comorbidities, incidence of CI-AKI remains high. In this review, pathophysiology of CI-AKI, its relationship with different types of CM, role of serum and urinary biomarkers for diagnosing CI-AKI, and various prophylactic strategies used for nephroprotection against CI-AKI are discussed in detail.